Chemistry and Chemical Reactivity, 10th Edition - John Kotz (Cengage Learning, 2018)
Succeed in chemistry with the clear explanations, problem-solving strategies, and dynamic study tools of CHEMISTRY & CHEMICAL REACTIVITY. Thorough instruction helps you develop a deeper understanding of general chemistry concepts through an emphasis on the visual nature of chemistry and the close interrelationship of the macroscopic, symbolic, and particulate levels of chemistry. The art program illustrates each of these levels in engaging detail.. Interactive study aids in OWLv2, such as Interactive Examples and Adaptive Learning Activities, help you master concepts.